2016
DOI: 10.1186/s13287-016-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved osteogenesis and upregulated immunogenicity in human placenta-derived mesenchymal stem cells primed with osteogenic induction medium

Abstract: BackgroundMesenchymal stem cells (MSCs) are widely used in cell-based therapy owing to their multilineage potential and low immunogenicity. However, low differentiation efficiency and unpredictable immunogenicity of allogeneic MSCs in vivo limit their success in therapeutic treatment. Herein, we evaluated the differentiation potential and immunogenicity of human placenta-derived MSCs manipulated with osteogenic priming and dedifferentiation process.MethodsMSCs from human placentas were subjected to osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…More important than cell surface expression levels is functional immunogenicity, which is the response of immune cells to the differentiated cells. Differentiated MSC have been shown to elicit allogeneic lymphocyte proliferation after osteogenic ( 34 ), chondrogenic ( 29 , 35 ), and hepatocytic ( 30 ) differentiation, and lymphocyte IFN-γ production in vitro after hepatocytic differentiation ( 30 ). Contrary to these studies, it has also been recently shown that differentiated MSC do not induce allogeneic T cell proliferation in vitro after osteogenic ( 36 ) or chondrogenic ( 37 ) differentiation.…”
Section: Immunogenicity and Immunomodulatory Potential Of Allogeneic mentioning
confidence: 99%
See 1 more Smart Citation
“…More important than cell surface expression levels is functional immunogenicity, which is the response of immune cells to the differentiated cells. Differentiated MSC have been shown to elicit allogeneic lymphocyte proliferation after osteogenic ( 34 ), chondrogenic ( 29 , 35 ), and hepatocytic ( 30 ) differentiation, and lymphocyte IFN-γ production in vitro after hepatocytic differentiation ( 30 ). Contrary to these studies, it has also been recently shown that differentiated MSC do not induce allogeneic T cell proliferation in vitro after osteogenic ( 36 ) or chondrogenic ( 37 ) differentiation.…”
Section: Immunogenicity and Immunomodulatory Potential Of Allogeneic mentioning
confidence: 99%
“…For example, hepatocyte differentiated MSC induced significantly more CD3 + and CD45 + cells after transplantation compared to undifferentiated MSC, despite the fact that the differentiated MSC exerted a beneficial effect on the glycemic control of the treated animals ( 33 ). Osteogenically differentiated MSC transplantation resulted in significantly more activated immune cells after implantation in a mouse model ( 34 ). In a diabetic model, evidence for in situ differentiation was observed, increased numbers of cytotoxic cells in recipients and higher levels of allo-antibody were attributed to this differentiation ( 40 ).…”
Section: Immunogenicity and Immunomodulatory Potential Of Allogeneic mentioning
confidence: 99%
“…They can undergo osteogenic differentiation when cultured in the traditional osteogenic medium or stimulated by the osteogenic growth factors (e.g., bone morphogenic proteins) in vitro [11]. When grafted in combination with osteoinductive scaffolds, they are able to form bone tissue at the ectopic sites [12, 13]. Noticeably, they also enhanced bone regeneration after transplantation at the bone defects [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the reciprocal relationship between adipogenesis and osteogenesis from MSCs is determined by a combination of regulatory signaling pathways induced by bone marrow niche; however, there are some missing links that exit within this complex stimuli. It has been appropriately demonstrated that lineage-specific transcriptional regulators, RUNX2, DLX5 and Osterix, favor osteoblasts 8 , 9 , whereas the CEBP (CCAAT/enhancer binding protein) family (α, β, δ) and PPARγ2 (peroxisome proliferator-activated receptor-γ2) favor adipocytes 10 , 11 . However, the commitment of adipogenesis over osteogenesis or vice versa and the transdifferentiation process of the committed cell type, particularly under pathological conditions, is still not clear.…”
Section: Introductionmentioning
confidence: 99%